2014
DOI: 10.1097/qai.0000000000000317
|View full text |Cite
|
Sign up to set email alerts
|

Clinic-Based Routine Voluntary HIV Testing in a Refugee Settlement in Uganda

Abstract: We implemented and evaluated a clinic-based routine voluntary HIV testing intervention in Nakivale Refugee Settlement in Uganda. Comparing the SOC period (40 days) to the Intervention period (168 days), the mean HIV-infected clients identified per week increased from 0.9 to 5.6, and there was no significant difference between the HIV prevalence in the two periods (standard of care: 3.3%, intervention: 4.5%; p > 0.5). Clinic-based routine HIV testing in a refugee settlement is effective and should be considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 13 publications
1
33
0
Order By: Relevance
“…The percentage of men out of total persons tested was reported in 25 home HTC studies 5,14,18,29,31,32,37,38,41–45,63,64,66,6872,8890 , two home with self-testing 11,75 , 10 mobile 10,13,68,72,9199 , 3 index partner 47,49,88 , 3 campaign 46,47,76 , 2 workplace 100,101 , 20 facility VCT 52,54,61,64,81,88,89,92,93,95,96,98,102107 , and 13 facility PITC 58,60,82–84,86,99,108113 (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The percentage of men out of total persons tested was reported in 25 home HTC studies 5,14,18,29,31,32,37,38,41–45,63,64,66,6872,8890 , two home with self-testing 11,75 , 10 mobile 10,13,68,72,9199 , 3 index partner 47,49,88 , 3 campaign 46,47,76 , 2 workplace 100,101 , 20 facility VCT 52,54,61,64,81,88,89,92,93,95,96,98,102107 , and 13 facility PITC 58,60,82–84,86,99,108113 (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of testers who were young adults testers <age 25 or <30 years) was reported in 17 home HTC studies 5,18,2931,35,37,38,45,63,64,6870,73,74,90,117 , one home with self-testing 11 , 13 mobile 10,12,13,68,91,93,9597,103,107,114 , two index partner 48,88 , two campaign 47,77 , 20 facility VCT 12,51,52,54,64,88,89,9193,95,104107,114,118120 , and six facility PITC 58,82,86,88,110,113 . Results varied considerably by study (Supplementary Figures S29–S35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were tested if they requested an HIV test or presented with signs and symptoms that led a clinician to refer them for a test. Though broader data on the prevalence of HIV/AIDS in the Nakivale settlement during the study period are not available, a subsequent study showed a prevalence of 3.3–4.5% (O'Laughlin et al, 2014). Prevalence rates in the refugees' countries of origin range from 1.1–6.3% (UNAIDS 2010).…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a clinic-based HIV screening intervention study at Nakivale Health Center [7]. Our primary objective for this analysis was to evaluate the correlates of HIV infection of those tested during this screening intervention.…”
Section: Introductionmentioning
confidence: 99%